Advanced CaZrO3-MgO Ceramic Compositions for High Responsability Applications - Nunes-Pereira, João (2018)
The development of new advanced materials for harsh environment operation conditions, such as high temperature, wear and severe erosion and corrosion, is of growing interest, namely for transport and energy industries, due to the ecological and energetic current concerns on a global scale. Particularly, in aerospace industry the increase of working temperature of engines and turbines combined with weight reduction will give rise to higher thrust and lower fuel consumption and consequently less emissions. [...]